Women and development in the Third World - Momsen, Janet Henshall (Routledge, 1991)
For all societies, the common denominator of gender is female subordination. For women of the Third World the effects of this position are worsened by economic crisis, the legacy of colonialism, as well as patriarchal attitudes and economic crises. Feminist critique has introduced the gender factor to development theory, arguing that the equal distribution of the benefits of economic development can only be achieved through a radical restructuring of the process of development. This important new book reviews both policy and practice in Latin America, Africa and Asia and raises thought-provoking questions concerning the role of development planning and the empowerment of women.